Association of medication adherence with cognitive Status in patients with chronic kidney disease - VIJI. P. C,; SREEJITH. K,; DR M. SREELATHA, (International Journal of Pharma and Bio Sciences, 2017)
Chronic kidney disease is emerged as a new risk factor of cognitive impairment. A cross-sectional, observational, questionnaire based study was conducted at Nephrology department of Govt. Medical College, Calicut. Morisky medication adherence questionnaire was used to assess medication adherence and Montreal Cognitive Assessment Questionnaire was used to assess cognitive status. Patient’s divided into 5 groups depending on stage of chronic kidney disease. Estimated glomerular filtration rate was calculated using Modification of diet in renal disease equation. Results found as 51.4% are highly adherent to therapy, followed by 38.1% with medium adherence and 10.5% with low adherence. 53.8% have mild cognitive impairment and 46.2% have normal cognitive status. Medication adherence with cognitive status was found to be statistically significant (P=0.000). We concluded that there is a significant association between medication adherence and cognitive status. Patients with higher medication adherence have less cognitive impairment.